The DREAM Act and Neoliberal Practice: Retrofitting Hispanic Immigrant Youth in U.S. Society - Aguirre, Jr (Social justice, 2011)
The article examines how neoliberal ideology has influenced U.S. public education for immigrant youth as well the U.S. DREAM (Development, Relief, and Education for Alien Minors) Act. The author defines neoliberalism as a set of political and economic practices based on the beliefs that markets should be privatized and an emphasis on market efficiency and accountability. Particular attention is given to zero-tolerance discipline policies, the marketization of education that focuses on performance and competition between schools, and charter schools.